Improving Mathematics Learning Outcomes Using Discovery Learning in Class XI Software Engineering 1 INFOKOM Bogor Vocational High School - Putri Riandini (International Journal of Social Service and Research, 2022)
This study aims to determine how to improve mathematics learning outcomes by using the Discovery Learning learning model. This research is Classroom Action Research (CAR). This research was conducted in 2 cycles, namely, cycle 1 and cycle 2. The research was carried out at Vocational High School INFOKOM Bogor class XI Software Engineering (RPL) 1 with a total of 25 students, consisting of 17 male and 8 female students. In pre-cycle activities, the average score obtained by students was 59.4, with the number of students who completed 9 people (36%). In cycle 1 activities, the average value of students obtained increased to 70.6 with the number of students who completed increased to 14 people or by 56%. In cycle 2, the average score of students increased to 90.6, with the number of completed students increasing to 22 (88%). Referring to the results obtained in cycles 1 and 2, it can be concluded that the Discovery Learning learning model can improve mathematics learning outcomes in class XI Software Engineering 1 Vocational High School INFOKOM Bogor.